Autologous Chondrocyte Implantation: Past, Present, and Future. Issue 2 (June 2016) - Welch, Tyler; Mandelbaum, Bert; Tom, Minas
Abstract : Focal cartilage defects of the knee are relatively common and may increase the risk of developing osteoarthritis. Autologous chondrocyte implantation (ACI) aims to restore the integrity of isolated cartilage lesions through the induction of hyaline-like cartilage formation. Although ACI has traditionally been used as a second-line treatment, recent evidence suggests that ACI should be considered as a first-line treatment option in certain patients. Recent controlled trials also suggest that there are improved clinical outcomes among those patients who undergo ACI over the mid-term and long-term compared with those treated with microfracture or osteochondral autograft/mosaicplasty, regardless of lesion size. Recent literature also indicates that arthroscopic, second-generation and third-generation techniques are associated with better outcomes and fewer complications than first-generation ACI. In summary, ACI is an effective tool for cartilage restoration that may be more efficacious and durable than other cartilage restoration techniques for appropriate candidates.